Metallic Mysteries: Deciphering Their Contribution to Alzheimer’s Pathogenesis (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Alzheimer’s disorder is the most prevalent type of insanity. It can start with a slight loss of memory and progress to a loss of response to stimuli and interaction. Deregulation of the antioxidant response and neurotransmission has been linked to neuro-decadence illnesses, likely Alzheimer’s disorder. Metals, along with microelements, support the proper operation of the nervous system. Heavy and essential metals both increase tau protein hyperphosphorylation and Aβ assemblage. The root of Alzheimer’s disorder is summarized in this article, along with the roles played by daily exposure to substances like pesticides and some macro and microelements. So, by knowing them, we can limit their exposure of them in day-to-day life. Gaining insight into these functions in brain health and illness could lead to discovering new curative targets for neuro-decadence diseases. Since metal ions are implicated in most degenerative diseases, future treatments may target them. One method is to limit the ions’ ability to obstruct oxidative processes or disturb protein folding by chelating and sequestering them.